Proceedings of the 4th International Conference on Management, Economics and Business (ICMEB 2019) 2020
DOI: 10.2991/aebmr.k.200205.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Entrepreneurship Education, Family Environment and Self-Efficacy on Students Entrepreneurship Intention

Abstract: This study aims to analyze the effect of entrepreneurship education, family environment and self-efficacy on the interests of student entrepreneurship. The population in this study were 365 students of Management at the University of Mercu Buana Jakarta. The sample used was 191 respondents, calculated based on Slovin formula. The sampling method uses convenience sampling. The method of collecting data uses a survey method, with the research instrument being a questionnaire. Data analysis method uses Partial Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 2 publications
1
6
0
3
Order By: Relevance
“…Effective entrepreneurship education can encourage the growth of interest in entrepreneurship. While the results of research conducted by Lekoko et al (2012); Hutasuhut (2018);and Sandi & Nurhayati (2020) found entrepreneurship education had no significant effect on entrepreneurial interest.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Effective entrepreneurship education can encourage the growth of interest in entrepreneurship. While the results of research conducted by Lekoko et al (2012); Hutasuhut (2018);and Sandi & Nurhayati (2020) found entrepreneurship education had no significant effect on entrepreneurial interest.…”
Section: Introductionmentioning
confidence: 92%
“…Environmental factors (in this case the family environment) are factors that significantly influence one's interest in entrepreneurship (Hutagalung et al, 2017;Novita et al, 2017;Wiani et al, 2018;Nurmaliza et al, 2018;Periansya, 2018;Ayyubi et al, 2018). However, a number of studies also found different results, where the environment does not affect a person's interest in entrepreneurship (Sandi & Nurhayati, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…A variety of models have been extended and adjusted to incorporate self-efficacy as a major factor in determining whether or not an individual intends to engage in entrepreneurial activity ( Ahmed et al, 2020 ; Urban, 2020 ; Liang et al, 2021 ; Westhuizen and Awotunde, 2021 ). For example, Sandi and Nurhayati (2020) took self-efficacy as a key antecedent to influencing EI and explored how factors such as entrepreneurship education and family environment affected the formation of EI by influencing ESE. The empirical results illustrated that self-efficacy has a significant impact on the interest of student entrepreneurship.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Family environment is defined as the closest social environment of an entrepreneur, which role is significant in shaping the character of a child, including entrepreneurial character [9]. In the family environment, a child gets inspiration and entrepreneurial support from the family, and there are activities in the family which lead to learning entrepreneurship [10].…”
Section: Theoretical Review and Hypothesismentioning
confidence: 99%